LEGALITY AND IMPACT ON SAVINGS AND LOAN COOPERATIVES IN MANAGING SAVINGS FROM NON-MEMBERS - Prabowo, M. Shidqon (Fakultas Hukum, Universitas Diponegoro, 2024)
The writing of this research aims to explain the legality or validity when the Savings and Loan Cooperative raises funds from members outside the cooperative, describes the authority and supervision measures by the Financial Services Authority (OJK) and the Ministry of Small and Medium Enterprise Cooperatives (KUKM) for cooperatives that collect savings funds outside of cooperative members and to clarify the legal consequences if the Savings and Loan Cooperatives collect savings funds outside cooperative members. This article uses a normative juridical approach method. For secondary data sources, the study of original legal texts, secondary legal literature, and non-legal sources can conclude that: 1. There is a legal basis used in raising funds for non-cooperative members, which is based on Article 44 of the Cooperative Act No. 25 of 1992. 2. OJK and KUKM have authority over cooperatives that collect savings funds outside cooperative members.3. There are legal consequences if the Savings and Loan Cooperative collects savings funds outside the cooperative members.